How and how well do workplace assessments work? Using contextual variations in a theory-based evaluation with a large N. (July 2021) - Dahler-Larsen, Peter; Sundby, Anna; Boodhoo, Adiilah
What can be said about effect of an intervention without a control group? The lack of evaluative evidence is a long-standing problem for regulatory policies against work-related health and safety risks. The European Union Occupational Safety and Health Framework has been in operation for three decades and covers more than 200 million workers, but the most recent evaluation was inconclusive about the benefits generated by this framework. A theory-based evaluation focusing on mechanisms in combination with a design capturing within-intervention variations offers a way forward. The idea is to measure the prevalence of most likely mechanisms and their correlation with outcomes. This approach is illustrated in a large- N evaluation of the use of workplace assessments in the public sector in Denmark. The strengths and weakness of the workplace assessment legislation are assessed. It is shown how findings based on the presented approach contribute to the public debate about workplace assessments.